Smart insects repeller - Suzi Seroja Sarnin; Nur Jumaatul Hidayati Binti Mohammad; Nani Fadzlina Naim; Norsuzila Ya’acob; Azlina Idris; Wan Norsyafizan Wan Mohamad; Mohd Nor Md Tan (Institute of Advanced Engineering and Science, 2020)
One of the key issues for those involved in farming and greenhouse is the use of pesticides. In a recent headline, there has been an epidemic of insect infestation that has destroyed 211 hectares of rice plants. These concerns have led to the discussion of possible over-use of pesticides that are not just killing dangerous pests, but also other animals that help combat the pest. In order to overcome the problem, a research was conducted by introducing a smart insect killer. In this developing project, Pyroelectric (PIR) sensor will be using as a motion detector towards insects. This sensor plays a role to transmit the signal for action in taking care of the plant. The IR sensors will install around the plant, so that it has good range to detect any motion. As a result, suitable chemical spray will trigger to repel these insects. A light emitting diode as an indicator of functional to the system.